A review on delayed toxic effects of sulfur mustard in Iranian veterans - mansour Razavi, Seyed (BioMed Central, 2012)
Iranian soldiers were attacked with chemical bombs, rockets and artillery shells 387 times during the 8-years war by Iraq (1980–1988). More than 1,000 tons of sulfur mustard gas was used in the battlefields by the Iraqis against Iranian people. A high rate of morbidities occurred as the result of these attacks. This study aimed to evaluate the delayed toxic effects of sulfur mustard gas on Iranian victims. During a systematic search, a total of 193 (109 more relevant to the main aim) articles on sulfur mustard gas were reviewed using known international and national databases. No special evaluation was conducted on the quality of the articles and their publication in accredited journals was considered sufficient. High rate of morbidities as the result of chemical attacks by sulfur mustard among Iranian people occurred. Iranian researchers found a numerous late complications among the victims which we be listed as wide range of respiratory, ocular, dermatological, psychological, hematological, immunological, gastrointestinal and endocrine complications, all influenced the quality of life of exposed victims. The mortality rate due to this agent was 3%. Although, mortality rate induced by sulfur mustard among Iranian people was low, variety and chronicity of toxic effects and complications of this chemical agent were dramatic.